Difference Doppler Centroid Estimation Method with High Spatial Resolution - Dukhopelnykova, Ie. V. (Видавничий дім «Академперіодика», 2012)
An easy and high-precision technique is proposed for Doppler centroid estimating in any SAR image point. Theoretical justification and using rules are presented, as well as precision analysis and result of using with real radar data are shown.